Research skills training implementation and challenges in undergraduate students - Zahro', Anisatuz; Muzazzinah, Muzazzinah; Ramli, Murni (Journal of Education and Learning (EduLearn), 2025)
Research skills are skills that accommodate technological developments in the 21st century and the competencies that students need to be successful in academic and future careers. The main aim of this review is to explore the implementation and challenges in research skills training for undergraduate students. A systematic literature review (adopted the preferred reporting items for systematic review and meta-analysis (PRISMA) method to synthesize 12 selected articles published within 2019-2023 at the ERIC and Google Scholar databases. The finding shows several methods and approaches in training research skills, including practical systematization models, the 4C-ID model, research-based learning, constant supervisor assistance, working on projects independently, training in accessing and utilizing literature, and applying active learning theory. Limited resources, curriculum integration, and pedagogical effectiveness were common challenges in university students' research skills training. Therefore, students' assignments must introduce active learning and research practices. It is also necessary to integrate research practices into the undergraduate curriculum so that research skills training is more structured and optimum.